Mesoscopic structure of the stock market and portfolio optimization - Sebastiano Michele Zema; Giorgio Fagiolo; Tiziano Squartini; Diego Garlaschelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
The idiosyncratic (microscopic) and systemic (macroscopic) components of market structure have been shown to be responsible for the departure of the optimal mean-variance allocation from the heuristic 'equally-weighted' portfolio. In this paper, we exploit clustering techniques derived from Random Matrix Theory (RMT) to study a third, intermediate (mesoscopic) market structure that turns out to be the most stable over time and provides important practical insights from a portfolio management perspective. First, we illustrate the benefits, in terms of predicted and realized risk profiles, of constructing portfolios by filtering out both random and systemic comovements from the correlation matrix. Second, we redefine the portfolio optimization problem in terms of stock clusters that emerge after filtering. Finally, we propose a new wealth allocation scheme that attaches equal importance to stocks belonging to the same community and show that it further increases the reliability of the constructed portfolios. Results are robust across different time spans, cross-sectional dimensions and set of constraints defining the optimization problem
Keywords: C02; D85; G11; 330; Random matrix theory; Community detection; Mesoscopic structures; Portfolio optimization